Effects of hypersplenism on the outcome of hepatectomy in hepatocellular carcinoma with hepatitis B virus related portal hypertension - Chen, Xiao; Wang, Dong; Dong, Rui; Yang, Tao; Huang, Bo; Cao, Yanlong; Lu, Jianguo; Yin, Jikai (Frontiers in Surgery, 2023)
Background Although hepatectomy plus splenectomy is not regularly recommended for hepatocellular carcinoma (HCC) with portal hypertension related hypersplenism due to the high risk accompanied with surgical procedures for now. Many researchers still believe that hypersplenism is a controversial adverse prognostic factor for HCC patients. Thus, the primary objective of the study was to determine the effects of hypersplenism on the prognosis of these patients during and after hepatectomy. Methods A total of 335 patients with HBV-related HCC who underwent surgical resection as primary intervention were included in this study and categorized into three groups. Group A consisted of 226 patients without hypersplenism, Group B included 77 patients with mild hypersplenism, and Group C contained 32 patients with severe hypersplenism. The influence of hypersplenism on the outcome during the perioperative and long-term follow-up periods was analyzed. The independent factors were identified using the Cox proportional hazards regression model. Results The presence of hypersplenism is associated with longer hospital stays, more postoperative blood transfusions, and higher complication rates. The overall survival (OS, P = 0.020) and disease-free survival (DFS, P = 0.005) were significantly decreased in Group B compared to those in Group A. Additionally, the OS (P = 0.014) and DFS (P = 0.005) were reduced in Group C compared to those in Group B. Severe hypersplenism was a significant independent prognostic variable for both OS and DFS. Conclusion Severe hypersplenism prolonged the hospital stay, increased the rate of postoperative blood transfusion, and elevated the incidence of complications. Furthermore, hypersplenism predicted lower overall and disease-free survivals.